2015
DOI: 10.1021/acsami.5b10534
|View full text |Cite
|
Sign up to set email alerts
|

pH and Glutathione Dual-Responsive Dynamic Cross-Linked Supramolecular Network on Mesoporous Silica Nanoparticles for Controlled Anticancer Drug Release

Abstract: A dynamic cross-linked supramolecular network of poly(glycidyl methacrylate)s derivative chains was constructed on mesoporous silica nanoparticles via disulfide bond and ion-dipole interactions between cucurbit[7]urils and protonated diamines in the polymer chains. This kind of multifunctional organic-inorganic hybrid material with pH- and glutathione- (GSH-) stimuli responsiveness can be applied to anticancer drug delivery and controlled release. Good release performance toward doxorubicin hydrochloride (DOX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 58 publications
2
83
0
Order By: Relevance
“…Besides, to minimize the potential cell membrane destabilization caused by the crowded positive charges of polymer brushes on MOFs, we chose to employ cucurbit[7]uril (CB[7]) for specific binding to amino groups of the polymer brushes . Note that the binding of CB[7] to the positively charged amino groups follows a distinctive pH‐dependent manner, where the supramolecular interactions decrease dramatically at lower pH of tumor microenvironment due to the weakening of host–guest binding interactions . Hence, the electrostatically formulated UiO‐PGEDA/TPE&DOX/CB[7] complex could be subjected to structural rearrangement, potentially facilitating the release of DOX from the polymer brush decorated MOF architecture once entrapped in a subcellular pH gradient, eventually conducing to favorable drug transportation and drug release behaviors for ultimate anticancer outcome (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, to minimize the potential cell membrane destabilization caused by the crowded positive charges of polymer brushes on MOFs, we chose to employ cucurbit[7]uril (CB[7]) for specific binding to amino groups of the polymer brushes . Note that the binding of CB[7] to the positively charged amino groups follows a distinctive pH‐dependent manner, where the supramolecular interactions decrease dramatically at lower pH of tumor microenvironment due to the weakening of host–guest binding interactions . Hence, the electrostatically formulated UiO‐PGEDA/TPE&DOX/CB[7] complex could be subjected to structural rearrangement, potentially facilitating the release of DOX from the polymer brush decorated MOF architecture once entrapped in a subcellular pH gradient, eventually conducing to favorable drug transportation and drug release behaviors for ultimate anticancer outcome (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…The pH sensing functions are of prime importance in MSN-based triggered-release nanocarriers. In another study, DOX hydrochloride was released by responding to acidic tumour intracellular environment [55]. Indeed, many of hybrid materials prepared for controlled drug release on tumor location were often based on pH or glutathione (GSH) level changes because of acidic pH (5.0) and high GSH concentration levels (2−10 mM) on tumour intracellular environment compared with normal tissues [54].…”
Section: Therapeutic or Diagnostic Approachmentioning
confidence: 99%
“…The solution is then filtered, frozen, and lyophilized with mannitol (Kuo, 2005). A 2015 study utilized a hybrid nanoparticle consisting of a network of poly(glycidyl methacrylate) chains secured to a silica nanoparticle (Li et al 2015). Li et al found this type of hybrid nanoparticle to be an ideal anti-cancer drug carrier, specifically of DOX (Li et al 2015).…”
Section: Biodegradable Nanoparticlesmentioning
confidence: 99%
“…A 2015 study utilized a hybrid nanoparticle consisting of a network of poly(glycidyl methacrylate) chains secured to a silica nanoparticle (Li et al 2015). Li et al found this type of hybrid nanoparticle to be an ideal anti-cancer drug carrier, specifically of DOX (Li et al 2015). The DOX-loaded nanoparticles were effective in inhibiting the growth of the cancer cell line, A549 (Li et al 2015).…”
Section: Biodegradable Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation